Comparison between Cowpea, Vigna radiate L., Plants Differentiated from Explain Callus and Seeds Plants in their Ability to Produce Nitrogen-Fixing Nodules - AL-Qasab, Ghanyah Hiatham; Rasheed, Jamella Hazza (Journal for Research in Applied Sciences and Biotechnology, 2023)
In this study, callus was produced from leaves and stems explants of cowpea axenic seedlings grown on agar_ solidified MS medium supplemented with growth regulators. Medium used for callus production was MS+NAA 1.0 mg-1 +BA 0.5 mg-1. It sustioned shoots differentiation. Regenerants shoots were rooted easily in MS medium+ NAA 1.0 mg-1 +BA 0.5 mg-1, Roots were inoculated with cowpea rhizobium 321H inoculum for 10 minutes. The inoculated plants were placed on the surface of 15 ml agar solidifed NF medium, nodules were developed after 50 days of inoculation. They used for measurement of amino acids. Also, sections were prepared from these nodules to follow anatomical lvariations between nodules produced on seed-plants and plants produced from callus. seedlings growing on NF media were transferred to a mixture of soil and peatmoss.